Equine reproduction - McKinnon, A. O. (Wiley-Blackwell, 2011)
Now in a much-anticipated two-volume new edition, this gold-standard reference stands as the most comprehensive and authoritative text on equine reproduction. Serving theriogenologists, practitioners and breeders worldwide as a one-stop resource for the reproductive assessment and management of equine patients, Equine Reproduction, Second Edition provides detailed information on examination techniques, breeding procedures, pregnancy diagnosis and management, reproductive tract diseases and surgery, and foaling. For the Second Edition, the stallion, mare and foal sections have been thoroughly u